Management of Lower Urinary Tract Dysfunction in Multiple Sclerosis: A Systematic Review and Turkish Consensus Report - TARCAN, TUFAN (WILEY, 2013)
AimsSince lower urinary tract dysfunction (LUTD) related to multiple sclerosis (MS) has a different behavior pattern than other types of neurogenic voiding dysfunction, we aimed to prepare a national consensus report for the management of LUTD due to multiple sclerosis in light of available literature. MethodsA search of available databases yielded an evidence base of 125 articles after the application of inclusion/exclusion criteria. When sufficient evidence existed, recommendations A (high), B (moderate), or C (low) were made according to the strength of evidence; recommendation D was provided when insufficient evidence existed. ResultsAvailable data did not support the use of invasive urodynamics in the initial evaluation of patients with MS and LUTD. Clinical studies on the safety and efficacy of antimuscarinics and alpha-blockers in these patients were scarce and low quality. Desmopressin could be used in MS-related overactive bladder symptoms owing to its short-term effects as an adjunctive treatment. Intravesical botulinum toxin type A treatment in patients with MS and detrusor overactivity was recommended in cases of medical treatment failure or severe side effects due to antimuscarinics. Pelvic floor rehabilitation together with neuromuscular electrical stimulation was also recommended as it increased symptomatic treatment success. This systematic review was not able to find any evidence-based cut off post-void residual value for the recommendation to start clean intermittent catheterization in MS-related LUTD. ConclusionsPatients with MS and LUTD could be best managed through the use of this consensus report. Neurourol. Urodynam. 32:1047-1057, 2013. (c) 2013 Wiley Periodicals, Inc.
Keywords: LUTS; neurogenic bladder; multiple sclerosis; urodynamics; systematic review; NEUROGENIC DETRUSOR OVERACTIVITY; BOTULINUM-A TOXIN; NEUROMUSCULAR ELECTRICAL-STIMULATION; PELVIC FLOOR REHABILITATION; RANDOMIZED CONTROLLED-TRIAL; DORSAL COLUMN STIMULATION; QUALITY-OF-LIFE; BLADDER DYSFUNCTION; DOUBLE-BLIND; VESICOURETHRAL DYSFUNCTION